A case of anaplastic lymphoma kinase (ALK)‐positive ciliated muconodular papillary tumor (CMPT) of the lung. Issue 2 (17th January 2017) - Taguchi, Ryo; Higuchi, Kayoko; Sudo, Motohiro; Misawa, Kenji; Miyamoto, Takashi; Mishima, Osamu; Kitano, Morihisa; Azuhata, Koji; Ito, Nobuo
Abstract : Ciliated muconodular papillary tumor (CMPT) is a rare papillary tumor that arises in the peripheral lung fields and is associated with the proliferation of ciliate d and goblet cells and increased mucin production. We report a case of CMPT involving the rearrangement of the anaplastic lymphoma kinase (ALK) gene. The patient was an 84‐year‐old Japanese female who had exhibited a small nodular shadow on chest computed tomography during a regular checkup 10 years ago. She underwent a partial resection of segment S10 of the right lung. The cut surface of the surgical specimen revealed a well‐circumscribed, jelly‐like mass measuring 8 × 8 × 10 mm. Histologically, the tumor was composed of a mixture of ciliated, goblet, and basal cells arranged in a papillary pattern together with pools of mucin. A diagnosis of CMPT was made. The lung tumor cells were subjected to fluorescent in situ hybridization and highly sensitive immunohistochemical staining for the ALK protein, both of which produced positive results. CMPT usually follows a favorable course, but the exact nature of this tumor; i.e., whether it is benign or malignant, has not been established. This is the first reported case of an ALK‐positive CMPT.